Highly Sensitive Colorimetric Detection of Early Stage Aluminum Corrosion in Water Using Plasmonic Gold Nanoparticle Films. Issue 21 (24th August 2018) - Tesler, Alexander B.; Sannomiya, Takumi; Vaskevich, Alexander; Sabatani, Eyal; Rubinstein, Israel
Abstract: Corrosion remains the major reason for the failure of metallic parts. Therefore, spotting and evaluating the severity of corrosion at its early stages is of great importance. Herein, a novel optical corrosion probe based on plasmonic gold nanoparticles immobilized on aluminum surface is demonstrated. The measurements confirm that the corrosion rate and mechanism of bare aluminum is identical to that of the developed probe. During Al corrosion, the gold nanoparticles are located entirely at the interface between the inner dense and outer porous layers of the formed aluminum oxide. The growth of the inner oxide layer during corrosion prompts a change in the reflection spectra and the appearance of strong coloration that is easily observed by the naked eye. Numerical modeling reveals that these optical changes occur mainly due to light interference within the inner oxide layer, which is located between the plasmonic gold nanoparticles and the underlying reflective aluminum. The ability of the plasmonic probe is further demonstrated to monitor the aqueous corrosion of thin films, bulk and alloyed Al, as well as Al protected by a self‐assembled monolayer of hydrophobic surfactant, and, hence, the wide applicability of the method. Abstract : The early stages of Al corrosion in water are monitored using a novel optical plasmonic probe. During Al corrosion, a dense layer of pseudoboehmite accumulates between the gold nanoparticles and the metal. Interference between the gold nanoparticles and the underlying metal causes a significant change in both the reflectance spectra and coloration of the probe.